Proceedings of the Second ACM-IEEE International Symposium on Empirical Software Engineering and Measurement 2008
DOI: 10.1145/1414004.1414051
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid faulty module prediction using association rule mining and logistic regression analysis

Abstract: This paper proposes a fault-prone module prediction method that combines association rule mining with logistic regression analysis. In the proposed method, we focus on three key measures of interestingness of an association rule (support, confidence and lift) to select useful rules for the prediction. If a module satisfies the premise (i.e. the condition in the antecedent part) of one of the selected rules, the module is classified by the rule as either faultprone or not. Otherwise, the module is classified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The association rule mining has been proposed as a non-model based (rule-based) prediction method (Kamei et al, 2008). Unlike the regression models which require the dependent and independent variables to be clearly defined and consequently force the analyst to priorly well-defines the questions and hypotheses the association rule mining can extract relations among the variables for which no questions have been formulated.…”
Section: Spatial Association Rule Miningmentioning
confidence: 99%
“…The association rule mining has been proposed as a non-model based (rule-based) prediction method (Kamei et al, 2008). Unlike the regression models which require the dependent and independent variables to be clearly defined and consequently force the analyst to priorly well-defines the questions and hypotheses the association rule mining can extract relations among the variables for which no questions have been formulated.…”
Section: Spatial Association Rule Miningmentioning
confidence: 99%
“…This becomes a problem when matched rules had different consequents (faulty and not-faulty). A typical way to handle this situation is to classify the module by the majority of rules' consequent [7]. Another way is to select the longest rules among matched rules [22].…”
Section: B Fault-prone Module Prediction By Rulesmentioning
confidence: 99%
“…In such cases, Kamei et al proposed to conduct a modelbased prediction as a complementary method [7].…”
Section: B Fault-prone Module Prediction By Rulesmentioning
confidence: 99%
“…In addition, they have been widely used in prediction models to determine how faulty classes will be during the testing phase, showing their ability to predict fault-proneness. [3]- [8] (see Fig. 1…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they have been related to managerial factors such as productivity, re-work effort for reusing classes and design effort and maintenance effort [1], [2]. In addition, the CK metrics, when measured from the code, have shown their ability to predict fault-prone code in several empirical studies [3]- [8]. Most of the results of these studies have found that coupling measures, such as RFC, are strongly related to fault-proneness code.…”
Section: Introductionmentioning
confidence: 99%